Electron Microscopy Studies of Cell-Wall-Anchored Cellulose (Avicel)-Binding Protein (AbpS) from Streptomyces reticuli - Walter, Stefan (American Society for Microbiology, 1999)
Streptomyces reticuli produces a 35-kDa cellulose (Avicel)-binding protein (AbpS) which interacts strongly with crystalline cellulose but not with soluble types of cellulose. Antibodies that were highly specific for the NH(2)-terminal part of AbpS were isolated by using truncated AbpS proteins that differed in the length of the NH(2) terminus. Using these antibodies for immunolabelling and investigations in which fluorescence, transmission electron, or immunofield scanning electron microscopy was used showed that the NH(2) terminus of AbpS protrudes from the murein layer of S. reticuli. Additionally, inspection of ultrathin sections of the cell wall, as well as biochemical experiments performed with isolated murein, revealed that AbpS is tightly and very likely covalently linked to the polyglucane layer. As AbpS has also been found to be associated with protoplasts, we predicted that a COOH-terminal stretch consisting of 17 hydrophobic amino acids anchors the protein to the membrane. Different amounts of AbpS homologues of several Streptomyces strains were synthesized.